Differences And Relations Between Meda, Majja And Vasa With Their Modern Aspects. - Kumar, Hemant; Sharma, Rajesh Kumar; Sharma, Dinesh Chandra (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda is a practical and reliable ocean of knowledge and every word written in ancient texts of Ayurveda is totally right. Adipose tissue was earlier known only as depot of fat but different researches proved it much more than just a fat store. But Acharyas in their texts wrote this earlier before the modern science proved it. According to anatomical positions, and compositions, Acharyas divided them into Meda (fat), Majja (bone marrow) and Vasa Adipose tissue). Now a days Meda (fat) can be called as visceral fat, Majja as bone marrow and Vasa as intramuscular fat. These three are having effect on other tissues of body like Meda is responsible for formation and nutrition of Asthi dhatu (bone) and Majja is responsible for formation of Shukra dhatu (semen). And hence this shows functional interdependence of between different tissues of body. The praman (evidence) of these tissues is also given and disturbances caused due to their increased or decreased level is also given. This shows importance of different tissues in maintaining equilibrium of the body. This review article is an attempt to explore the physiological aspects of Meda (fat), Majja (bone marrow) and Vasa (Adipose tissue). Differences and relations between these three are described in this article. Different researches in modern science are also mentioned here to show how the views of Acharyas are accepted globally.